Female prostitution in urban Russia, 1900-1917 - Hearne, Siobhan (2018)
This thesis examines the social history of female urban prostitution in the final years of the Russian empire (1900-1917). During this period, the tsarist authorities legally tolerated prostitution under a system named regulation (reglemantatsiia) or the medical-police supervision of prostitution (vrachebno-politseiskii nadzor za prostitutsiei). The stated aim of regulation was to reduce levels of venereal disease, yet in practice the system functioned rather to control the movement and settlement of prostitutes by making them known to the authorities. This thesis focuses on the different groups that the rules of regulation directly affected, including prostitutes, their clients, their managers, and wider urban communities. It examines specific urban spaces, the state-licensed brothel, and the lives of registered prostitutes and their clients. This approach allows an exploration of how the system operated in practice and how the regulation of prostitution fitted within wider attempts by the imperial state to monitor lower-class people. In doing so, this thesis contributes to the growing literature on sexuality, on the intersections of gender and class, and on the experiences of lower-class people in late imperial Russia.